Multi-tiered systems of support in secondary schools the definitive guide to effective implementation and quality control - Clark, Alison G.; Dockweiler, Katherine A. (Routledge, 2019)
"Multi-Tiered Systems of Support in Secondary Schools is a humanistic guide used to produce reliable human capital outputs while ensuring the promotion of socially just practices on campus. Featuring real perspectives from practitioners, this text shows how to make manageable changes at secondary schools in accordance with public policy mandates and evidence-based practices by developing smart teams and programs, identifying roles and responsibilities, implementing layers of academic support and services, improving behavioral and mental health of students, and creating an inclusive school culture. This unique guide assists practitioners in implementing systemic change in a bureaucratic system while simultaneously strengthening the health and cohesion of the organization"--Provided by publisher.